2022
DOI: 10.1111/jopr.13482
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Flexural Strength Discrepancies Between Milled and Lithography‐Based Additively Manufactured Zirconia

Abstract: Purpose To evaluate the chemical composition, flexural strength, and Weibull characteristics of milled and lithography‐based additively manufactured (AM) zirconia. Materials and methods A virtual design of a bar (25×4×2 mm) was completed using a software program. The standard tessellation language file was used to manufacture all the specimens: 3Y‐TZP zirconia (Priti multidisc ZrO2 monochrome) milled (M group) and 3Y‐TZP zirconia (LithaCon 3Y 210) lithography‐based AM (CeraFab System S65 Medical) (AM group) ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 32 publications
1
25
1
Order By: Relevance
“…A total of 16 in vitro studies were included in the qualitative analysis 35,42‐45,47,58‐67 43,45,58–61,66,67 alumina (3 studies)], 35,42,62 hardness [zirconia (2 studies), 58,64 alumina (2 studies)], 35,62 fracture toughness [zirconia (1 study), 64 alumina (2 studies)], 35,62 morphology [zirconia (2 studies), 58,64 alumina (1 study)], 62 roughness [zirconia, (2 studies)], 58,64 Weibull distribution [zirconia (2 studies), 59,61 alumina (2 studies)], 62,42 density [zirconia (2 studies)], 61,64 sintering shrinkage [zirconia (2 studies)], 61,42 structure [zirconia (4 studies)], 44,61,64,67 fracture resistance [zirconia (2 studies)], 47,65 load bearing capacity [zirconia (1 study)], 63 wettability [zirconia (1 study)], 64 biocompatibility [zirconia (1 study)], 64 elastic modulus [zirconia (1 study)], 44 and chemical composition [zirconia (2 studies)] 61,43 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 16 in vitro studies were included in the qualitative analysis 35,42‐45,47,58‐67 43,45,58–61,66,67 alumina (3 studies)], 35,42,62 hardness [zirconia (2 studies), 58,64 alumina (2 studies)], 35,62 fracture toughness [zirconia (1 study), 64 alumina (2 studies)], 35,62 morphology [zirconia (2 studies), 58,64 alumina (1 study)], 62 roughness [zirconia, (2 studies)], 58,64 Weibull distribution [zirconia (2 studies), 59,61 alumina (2 studies)], 62,42 density [zirconia (2 studies)], 61,64 sintering shrinkage [zirconia (2 studies)], 61,42 structure [zirconia (4 studies)], 44,61,64,67 fracture resistance [zirconia (2 studies)], 47,65 load bearing capacity [zirconia (1 study)], 63 wettability [zirconia (1 study)], 64 biocompatibility [zirconia (1 study)], 64 elastic modulus [zirconia (1 study)], 44 and chemical composition [zirconia (2 studies)] 61,43 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Meta‐analysis was performed for the flexural strength parameter with 7 out of the 11 studies that reported on flexural strength 42,43,45,58‐60,67 . Three studies were excluded because they had no control group, 61,62,66 and 1 study used a different testing method (biaxial flexural strength) 35 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations